A study of the release of the amphoteric drug amoxycillin from biodegradable polymers - Mollo, Ana Rosario (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2000)
Poly-alpha-hydroxy-aliphatic esters constitute a group of biodegradable polymers which have been actively investigated over the past three decades for the sustained release of drug compounds. A literature review revealed that the mechanisms of drug release from these esters had not yet been established for amphoteric compounds. Amoxycillin is a commonly used penicillin which was chosen as a model amphoteric drug, since sustained release antibiotics have potential commercial applications. Drug/polymer discs were compressed from either mechanical mixture of the raw powders (MM) or from films prepared through a solvent-evaporation procedure (SE), Four polymers of varying molecular weight and monomer composition were used in the investigation. Among the methods used to characterize the polymeric devices were differential scanning calorimetry (DSC), X-ray diffraction (XRD) and scanning electron microscopy (SEM). Drug release studies were carried out in phosphate buffer pH 5.9, with drug concentration measured by UV spectroscopy and high-performance liquid chromatography (HPLC). Polymer molecular weight and mass loss were evaluated during drug release, both in drug loaded and drug-free discs.
Keywords: Pharmaceutics, Ph.D.; Ph.D. Trinity College Dublin